Systemic triplet therapy for metastatic hormone-sensitive prostate cancer: A systematic review and network meta-analysis - Jian, Tengteng; Zhan, Yang; Hu, Kebang; He, Liang; Chen, Sunmeng; Hu, Rui; Lu, Ji (Frontiers in Pharmacology, 2022)
Purpose: To perform a systematic review and network meta-analysis to compare the efficacy and safety of currently available docetaxel-based systemic triplet therapies for metastatic hormone-sensitive prostate cancer (mHSPC). Methods: We searched for eligible publications in PubMed, Embase, and Cochrane CENTRAL. Improvements in overall survival (OS) and radiographic progression-free time (rPFS) were compared indirectly using network meta-analysis and evaluated using the surface under the cumulative ranking curve (SUCRA). Other secondary endpoints, such as time to castration-resistant prostate cancer and/or adverse events (AEs), were also compared and evaluated. Results: Five trials were selected and analyzed using a network meta-analysis. Compared to androgen deprivation therapy (ADT) plus docetaxel, darolutamide (hazard ratio [HR]: 0.68, 95% credible interval [CrI]: 0.57–0.80) and abiraterone (HR: 0.75, 95% CrI: 0.59–0.95) triplet therapy had significantly longer OS, and darolutamide triplet therapy was the first treatment ranked. Abiraterone (HR: 0.49, 95% CrI: 0.39–0.61) and enzalutamide (HR: 0.52, 95% CrI: 0.30–0.89) had significantly better rPFS than ADT plus docetaxel; however, all three therapies, including abiraterone, apalutamide, and enzalutamide, were the best options with a similar SUCRA. At most secondary endpoints, systemic triplet therapy was superior to ADT plus docetaxel. The risk of any AEs in darolutamide or abiraterone triplet therapy was comparable with ADT plus docetaxel (odds ratio [OR]: 2.53, 95% credible interval [CrI]: 0.68–12.63; OR: 1.07, 95% CrI: 0.03–36.25). Abiraterone triplet therapy had an increased risk of grade≥3 AEs (OR: 1.56, 95% CrI: 1.15–2.11). Conclusion: Systemic triplet therapy was more effective than ADT plus docetaxel for mHSPC. Of the triplet therapy regimens, darolutamide ranked first in terms of improved OS. Abiraterone and enzalutamide triplet ranked first in terms of rFPS, however, it did not confer a statistically difference among all triplet regimens. The overall risk of AEs was comparable. More studies are required for current and potential combinations of systemic triplet therapy.